Some Methodological and Conceptual Considerations in Studies of Auditory Imagery. Issue 1 (3rd April 2018) - Hubbard, Timothy L.
ABSTRACT: Methodological and conceptual issues in the study of auditory imagery are discussed, and these issues include the use of different measures in experiments on auditory imagery (questionnaires, behavioral tasks, physiological recordings), proliferation and ambiguity of terminology associated with auditory imagery (multiple terms for the same construct, failure to define many constructs), and distinctions regarding different aspects of auditory imagery (vividness, clarity, and control; inner ear and inner voice; format and activity; voluntary imagery and involuntary imagery; auditory information and nonauditory information). Caution in generalizing between different potential types, components, mechanisms, and processes of auditory imagery (e.g., inferring properties of involuntary auditory hallucinations based on characteristics of voluntary auditory imagery) is suggested. Whether findings previously attributed to auditory imagery necessarily resulted from auditory imagery or could have resulted from some other representational format is discussed, and ways to address this representational ambiguity are proposed (e.g., obtaining convergent evidence of imagery generation and use, reclassifying participants into imagery or non-imagery conditions based on debriefing). Parallels with analogous issues in visual imagery literature are noted. These issues are relevant to future studies of auditory imagery and also have implications for other topics within psychological science (e.g., motor theories of perception, working memory, embodied cognition).